Pertechnetates - a structural study across the periodic table - Strub, Erik; Grödler, Dennis; Zaratti, Daniele; Yong, Clarence; Dünnebier, Lisa; Bazhenova, Sonja; Roca Jungfer, Maximilian; Breugst, Martin; Zegke, Markus (Chemistry - a European journal, 2024)
The number of crystal structures of pertechnetates derived from aqueous solutions has been expanded from seven to over 30. We report the conversion of NH4TcO4 to aqueous HtcO4 via acidic cation exchange. This is followed by the synthesis and structural elucidation of pertechnetate salts of alkaline earth (AE), transition metal I and lanthanoids (Ln) elements. Various degrees of hydration and coordination are discussed. Where possible, a comparison with the perrhenate homologues is made. The described syntheses and materials may be used as novel starting materials for extended technetium research.
Zuerst veröffentlicht: 28. Februar 2024
Gesehen am 19.08.2024